Switching and emergence of CTL epitopes in HIV-1 infection - Han, Chungyong (BioMed Central, 2014)
BACKGROUND: Human Leukocyte Antigen (HLA) class I restricted Cytotoxic T Lymphocytes (CTLs) exert substantial evolutionary pressure on HIV-1, as evidenced by the reproducible selection of HLA-restricted immune escape mutations in the viral genome. An escape mutation from tyrosine to phenylalanine at the 135th amino acid (Y135F) of the HIV-1 nef gene is frequently observed in patients with HLA-A*24:02, an HLA Class I allele expressed in ~70% of Japanese persons. The selection of CTL escape mutations could theoretically result in the de novo creation of novel epitopes, however, the extent to which such dynamic “CTL epitope switching” occurs in HIV-1 remains incompletely known. RESULTS: Two overlapping epitopes in HIV-1 nef, Nef126-10 and Nef134-10, elicit the most frequent CTL responses restricted by HLA-A*24:02. Thirty-five of 46 (76%) HLA-A*24:02-positive patients harbored the Y135F mutation in their plasma HIV-1 RNA. Nef codon 135 plays a crucial role in both epitopes, as it represents the C-terminal anchor for Nef126-10 and the N-terminal anchor for Nef134-10. While the majority of patients with 135F exhibited CTL responses to Nef126-10, none harboring the “wild-type” (global HIV-1 subtype B consensus) Y135 did so, suggesting that Nef126-10 is not efficiently presented in persons harboring Y135. Consistent with this, peptide binding and limiting dilution experiments confirmed F, but not Y, as a suitable C-terminal anchor for HLA-A*24:02. Moreover, experiments utilizing antigen specific CTL clones to recognize endogenously-expressed peptides with or without Y135F indicated that this mutation disrupted the antigen expression of Nef134-10. Critically, the selection of Y135F also launched the expression of Nef126-10, indicating that the latter epitope is created as a result of escape within the former. CONCLUSIONS: Our data represent the first example of the de novo creation of a novel overlapping CTL epitope as a direct result of HLA-driven immune escape in a neighboring epitope. The robust targeting of Nef126-10 following transmission (or in vivo selection) of HIV-1 containing Y135F may explain in part the previously reported stable plasma viral loads over time in the Japanese population, despite the high prevalence of both HLA-A*24:02 and Nef-Y135F in circulating HIV-1 sequences.